Construction of Excellent Visible Light Absorption Heat Storage Slurry Using Phase Change Microcapsules for Solar Thermal Utilization. Issue 33 (5th September 2022) - Zhang, Qingqing; Sun, Zhicheng; Guo, Qingwei; Zhou, Yang; Li, Zhenzhen; Wen, Jinyue; Li, Furong; Liu, Yuanyuan; Jiao, Shouzheng
Abstract: Most solar thermal utilization materials can only absorb ultraviolet irradiation rather than visible‐light, limiting the photothermal conversion efficiency of corresponding devices. In this work, a functional thermal slurry system with excellent visible‐light absorption and high photothermal conversion performance is developed based on the phase change microcapsules, incorporating the visible‐light absorption antenna in the shell structure. Specifically, a phase change microcapsule with paraffin as the core material and silica as the wall material is prepared by the in‐situ polymerization method, in which the shell layer is doped with various photosensitive molecules. The photothermal conversion efficiency of copper phthalocyanine and MXene can reach 98 % and 85.3 % respectively. The corresponding conversion efficiency could reach up to more than 80 % in a long temperature range. Therefore, the doping of photosensitive molecules with visible‐light absorption can promote the solar energy conversion efficiency of these solar thermal utilization materials. Abstract : The combination of photosensitive dyes and phase change microcapsules significantly improves the efficiency of photothermal conversion. The dye converts light energy into heat, which is stored in phase‐change microcapsules and released when needed. The heat storage slurry doped with copper phthalocyanine and MXene have the best photothermal conversion performance and are expected to become a novel kind of heat collecting medium.